2012
DOI: 10.1016/j.virol.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic immune activation is a distinguishing feature of liver and PBMC gene signatures from HCV/HIV coinfected patients and may contribute to hepatic fibrogenesis

Abstract: Hepatitis C virus/human immunodeficiency virus (HCV/HIV) coinfected patients demonstrate accelerated progression to severe liver injury in comparison to HCV monoinfected patients, although the underlying mechanisms are unclear owing to infection of separate tissue compartments with two distinct viral pathogens. Microarray analysis of paired liver biopsy and peripheral blood mononuclear cell (PBMC) specimens from HCV/HIV coinfected and HCV monoinfected patients identified a gene expression signature associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Under the category of immune system, the most unique finding in our study is the significant up-regulation of cytotoxicity pathway in the former versus the latter group across the 3 pairwise comparisons (HH versus HIV, HH versus HCV, HIV versus HCV; FDR from <0.001 to 0.019; Figure 3; Table 2). Our study is the first to report the significant alterations of this pathway differentiating between HIV, HCV mono-and co-infection, which is also supported by previous findings in HIV/HCV co-infection [30,31,33,34]. Recently, two PBMC studies have implicated this pathway.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Under the category of immune system, the most unique finding in our study is the significant up-regulation of cytotoxicity pathway in the former versus the latter group across the 3 pairwise comparisons (HH versus HIV, HH versus HCV, HIV versus HCV; FDR from <0.001 to 0.019; Figure 3; Table 2). Our study is the first to report the significant alterations of this pathway differentiating between HIV, HCV mono-and co-infection, which is also supported by previous findings in HIV/HCV co-infection [30,31,33,34]. Recently, two PBMC studies have implicated this pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, two PBMC studies have implicated this pathway. One of them reported its enrichment in the significantly up-regulated genes in co-infected patients versus controls [34], and the other showed NK cell signaling in the expanded network constructed from the gene signature in HH versus HCV group [30]. In addition, the up-regulation of cytotoxicity pathway in HH versus HIV as well as in HIV versus HCV has been found in CD4+ T cells [31], and high percentages of cytotoxic CD8+ T cells associated with liver fibrosis in co-infected patients have been detected by the flow cytometry study [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, HIV-1 infection of CD4+ T cells has a profound effect in impairing adaptive immune responses towards HCV infected cells contributing to poor natural clearance of the virus [123]. A recent study has suggested that the chronic immune activation characteristic of HIV-1 infection and progression to AIDS [124,125] is a distinguishing feature of the host response to HCV/HIV-1 co-infection [126]. …”
Section: Potential Role Of Mirnas In Hcv/hiv-1 Co-infectionmentioning
confidence: 99%